The Intentional Base-on-ball Phenomenon in Baseball: A Statistical Analysis and Strategic Recommendations - Kappy, Andrew (University of Waterloo, 2005)
The game of baseball is amenable to a variety of strategies that affect short-term outcomes. This paper employs regression analysis, simulation, and cognitive analysis of mental biases to analyze the strategic scenario known as the "Intentional Base-on-Balls" and proposes a model to explain that strategy and predict its effectiveness.
The results of this study suggest that managers are prone to Type II errors, that is, issuing an Intentional Base-on-Ball in a situation where objective analysis suggests otherwise. Results further suggest that the ratio of Type I errors to Type II errors is disproportional to the ratio of their respective costs. This imbalance points to a subjective component to the decision-making process, one that can be explained by biases and cognitive errors.
The results and model described in this paper may allow managers to avoid future mistakes and improve their decision-making ability.
Keywords: Management